How was Felt Van Earthquake by a Neighbor University Hospital? - ZENGIN, Yilmaz (Turk J Emerg Med, 2016)
OBJECTIVES: Natural disasters, which are defined as events causing great damage or loss of life, are events of natural origin unpreventable by human beings that occur in a short period of time and lead to loss of life and property. The aim of the study is to analyze which patient groups and problems at a university hospital after the earthquakes in Van. METHODS: For the purposes of this study, 169 patients who presented to our emergency room following the earthquakes that occurred on the 23rd of October, 2011 and the 9th of November, 2011 in Van and were treated as an outpatient or inpatient were enrolled. Patients were divided into two groups. Patient data including the clinical and demographic characteristics were analyzed. RESULTS: Among the 169 patients included in our study, 97 (57.4%) were male and 72 (42.6%) were female. The mean age was 26.95±16.44 years in Group 1 and 39.80±23.08 years in Group 2. In our study, the majority of the patients in Group 1 had orthopedic injuries, while internal problems were more common in Group 2. The need for intensive care was greater among the patients in Group 1 compared to Group 2 (p<0.05). The leading cause of death in Group 1 was multi-systemic trauma in 7 out of the 10 patients (70%) and internal problems in Group 2 with 5 out of 12 patients (41.5%). CONCLUSIONS: Our country is in a geographical location where earthquakes are responsible for great losses of life and property. An efficient disaster relief plan may help to minimize the possible damage of earthquakes.